2016
DOI: 10.5038/1944-0472.9.4.1556
|View full text |Cite
|
Sign up to set email alerts
|

I SEE! Scotland: Tackling Sectarianism and Promoting Community Psychosocial Health

Abstract: . For over a decade, Eolene has developed and evaluated cognitive complexity interventions to reduce and prevent destructive conflict through participatory research and end-user partnerships in diverse communities, using the cross-culturally validated measure, integrative complexity (IC) (Suedfeld and Tetlock, 2014 AbstractWe developed and tested through two studies a new intervention run as a course, I SEE! Scotland, to reduce and prevent Protestant-Catholic sectarianism in Scotland, a historic intergroup co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Taken together, these results indicated that the course achieved its core goals, increasing participants' cognitive complexity, empathy, and resilience to build social cohesion and reduce the risk of extremism and interethnic tension. At the time of writing, the IC Thinking research group had assessed 83 similar IC interventions in nine countries, developed for each country context to address a range of extreme mindsets (Boyd-MacMillan, 2016;Boyd-MacMillan et al, 2016;Liht & Savage, 2013;Nemr & Savage, 2019;Savage et al, 2014Savage et al, , 2020. Results for these IC interventions show consistent significant gains in IC across sectarianism, extremisms, theological and intergroup conflict, cultural contexts, and participants from diverse educational backgrounds.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, these results indicated that the course achieved its core goals, increasing participants' cognitive complexity, empathy, and resilience to build social cohesion and reduce the risk of extremism and interethnic tension. At the time of writing, the IC Thinking research group had assessed 83 similar IC interventions in nine countries, developed for each country context to address a range of extreme mindsets (Boyd-MacMillan, 2016;Boyd-MacMillan et al, 2016;Liht & Savage, 2013;Nemr & Savage, 2019;Savage et al, 2014Savage et al, , 2020. Results for these IC interventions show consistent significant gains in IC across sectarianism, extremisms, theological and intergroup conflict, cultural contexts, and participants from diverse educational backgrounds.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, results from 103 assessed courses designed to increase cognitive complexity each show significant IC gain, including courses run in secondary schools in Scotland, Finland and Pakistan (reviewed in Boyd-MacMillan et al, 2016;Nemr & Savage, 2019;Peracha, Savage, Khan, Ayub, & Zahr, forthcoming). This body of research, leveraging and measuring IC, has been delivered across 10 countries to address a range of extremisms (Islamist, right wing, left wing, sectarianism, national separatism, and inter-group conflicts), showing cross-cultural replication, with each course adapted to context, using a process similar to the A, B, C, D stages described above (Boyd-MacMillan et al, 2016;Liht & Savage, 2013;Nemr & Savage, 2019;Peracha et al, forthcoming;Savage & Andrews Fearon, 2021;Savage, Liht, & Khan, 2014). Of this, LWWD is the first critical thinking course designed to increase cognitive complexity to address social polarisations or extreme thinking of any kind in secondary schools in England.…”
Section: Discussionmentioning
confidence: 99%
“…Each of the four cumulative sessions follows a four-stage A, B, C, D pattern (with A and B stages usually of equal duration to C and D stages) which developed through piloting the method over years in different contexts (Boyd-MacMillan, Andrews Fearon, Ptolomey, & Mathieson, 2016;Liht & Savage, 2013;Savage & Andrews Fearon, 2021). The A, B, C, D pattern is explained below in terms of how attention is shifted between Heart Thinking and Head Thinking through the type of stimuli per task, and later in the session to promote interaction between the two subsystems at higher levels of complexity.…”
Section: Operationalising Lwwd In Secondary Schoolsmentioning
confidence: 99%
“…15 Two studies with one hundred and four participants in Scotland found significant impact with medium to large size effects, alongside significant resilience gains. 16 All total, empirical assessments of fifty out of fifty runs of IC interventions, using pre-post testing, have found significant impact (increases in IC-more deliberate, flexible, open thinking-toward one's own and opposed groups). 17 Due to diversity in demographics and our commitment to action research (both requiring uncomplicated assessment designs with as low a burden for participants as possible), our assessment designs have been relatively simple to date.…”
Section: Underlying Theorymentioning
confidence: 99%
“…34 These experiences shape imaginations with hope for a future where differences do not prevent collaboration and dysfunctional feedback loops are replaced by intentional loops co-created collaboratively in the face of difference and disagreement. 35 (The time-frame/delivery schedule will be standardised in partnership with our end-user partner schools. )…”
Section: Assessment Instrumentsmentioning
confidence: 99%